Pengaruh Gadget Terhadap Kemampuan Interaksi Sosial Siswa Sekolah Dasar - Rini Budiwati; Murfiah Dewi Wulandari; Darsinah Darsinah (Jurnal Ilmiah Wahana Pendidikan, 2022)
Technological advances are increasingly complex and evolving. This has various implications on human life, including mentality and behavior. Gadgets are one of the technical innovations that have an impact on the human mind. Gadgets are electronic devices used for modern communication. In Indonesia, most children spend their time playing with electronic devices. Of course this has an impact on children's development, especially in terms of social interaction. The term "social interaction" refers to the relationships that occur among individuals who engage in social communication and activity. The purpose of this research is to examine how far the social interaction ability of elementary school students can be influenced by technology. The research strategy of qualitative descriptive research methods was applied in this study, and a review of various relevant reading materials according to the topic being investigated. According to research results, gadgets have an impact on the mind set and behavior of adults, as well as the behavior of children. Gadgets have a significant impact on the development of elementary school children and the development of their social interactions. Children's dependence on this technology due to prolonged use of devices, devices that are played for a relatively long duration and repeated every day, children will tend towards antisocial personality.